Extracts from Wheat, Maize, and Sunflower Waste as Natural Raw Materials for Cosmetics: Value-Added Products Reaching Sustainability Goals - Milica Lukić; Ana Ćirić; Dragana D. Božić; Jelena Antić Stanković; Đorđe Medarević; Zoran Maksimović (MDPI AG, 2024)
Agricultural waste is underutilized, and sometimes burning them has a negative impact on the environment and human health. This research investigates the untapped potential of extracts from maize, wheat and sunflower waste as natural materials for cutaneous, specifically, cosmetic application. The possibility of incorporating lipid and ethanol extracts from wheat, maize, and sunflower into creams was investigated together with their potential contribution to the structural and functional properties of the topical formulations. Results of the physicochemical characterization show that investigated extracts can be successfully incorporated into creams with satisfactory stability. All extracts showed a desirable safety profile and good antimicrobial activity against various microorganisms. Lipid extracts have proven to be promising structural ingredients of the oil phase, contributing to the spreadability, occlusivity, and emollient effect. Ethanol extracts influenced washability and stickiness of the formulation and could be considered as prospective ingredients in self-preserving formulations. The extracts affected the sensory properties of the creams, mainly the smell and color. These results suggest that the extracts from wheat, maize, and sunflower waste could be used as multifunctional natural ingredients for cosmetic formulations which can replace less sustainable raw materials. This also represents a valorization of waste and is in line with broader sustainability goals.